Developing Teaching Material Bajo’s Local Wisdom Sea Preservation Thomson-Brooks/Cole Model - HL, Nur Ihsan; Saputra, I Gede Purwana Edi; Sejati, Andri Estining; Syarifuddin, Syarifuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This research aims to identify the Bajo’s local wisdom in preservation sea and coastal area in the form of teaching material in the Basic Natural Science (BNS) focused on environment preservation. The type of research is research and development. Teaching material is arranged based on the principle and procedures of developing a 4-D model, there are: define, design, develop, and disseminate. Teaching material draft validated by two matter experts, one language experts, and one design expert. Teaching material draft tried to the Language and Literature Education students with 10 people in the small group and 40 people in the large group. The average validation results were 83.73% (very good) and did not need revision. Revised sections: cover, image source, chapter display, and change the unsuitable image. The small group student trials result obtained 80.68% (good) and large groups obtained 82.95% (good). The implication of this research is as an alternative solution to maintain and enhance the local wisdom value of the Bajo’s in preserving the sea and coast through teaching materials.